Inadequação da ingestão de nutrientes em idosos: resultados do estudo EPIDOSO - Pinto, Juliana Alexandre [UNIFESP] (2017)
INTRODUCTION: Population aging is occurring all over the world, bringing major political, economic and social challenges to the Health Sector. In this context, nutritional inadequacies can significantly compromise the health and quality of life of the elderly. OBJECTIVE: To evaluate the inadequacy of nutrients in the elderly and its association with demographic factors, chronic non communicable diseases and number of compromised daily life activities. METHODS: This is a cross-sectional study, nested with a cohort of elderly individuals from the EPIDOSO II project. The study included 596 elderly individuals who responded to the 24-hour recall. Nutritional variables (energy, carbohydrates, proteins, lipids, fibers, alcohol, vitamins A, B2, C, D, calcium, iron, zinc and sodium) were used as indicators of the inadequacy of nutritional variables. We determined a criterion of nutritional adequacy or inadequacy, where the sum of seven or more inadequacies of the nutritional variables points to nutritional inadequacy. Logistic regression models were used to evaluate the association between nutritional inadequacy and independent variables. RESULTS: Individuals aged ≥ 60 years, 412 women and 184 men, with a mean age of 72.3 years (sd=7.4), the mean BMI found was 27.3 kg/m2 (sd=4.8), 59.1% of individuals were classified as having nutritional inadequacy. Multiple logistic regression analysis showed a positive association between nutritional inadequacy and males (OR=1.60; 95%CI [1.11; 2.31]; p=0.011), age in years (an increase of 1 year of age increases the odds in 1.036; p=0.003), a separate marital status (OR= 2.12; 95%CI [1.14; 3.92]; p=0.017) and to have at least one compromised daily life activity (OR=1.55; 95%CI [1.07; 2.24]; p=0.020). CONCLUSION: Nutritional inadequacy was related to demographic factors and functional impairment. Knowing the factors that relate to nutritional inadequacies are of fundamental importance for the planning of health policies in nutrition.